R Pengaruh Pembelajaran STEM terhadap Literasi Sains Siswa Sekolah Dasar - Reni Violina Simanjuntak; Neni Hermita; M. Jaya Adi Putra (STKIP Subang, 2025)
This study aims to analyze the effect of STEM (Science, Technology, Engineering, and Mathematics) learning on elementary school students' scientific literacy. STEM learning is seen as an integrative approach that can develop conceptual understanding, critical thinking skills, and problem-solving abilities through exploratory, investigative, and project-based activities. The study used a quasi-experimental method with a pretest–posttest control group design on 60 elementary school students who were divided into experimental and control classes. The instrument used was a scientific literacy test that covered aspects of conceptual understanding, data interpretation, and the application of scientific knowledge in real-life contexts. The results showed that there was a significant increase in students' scientific literacy after participating in STEM learning. The experimental class experienced a significantly higher increase in scores than the control class, and the t-test results showed a p value = 0.000 < 0.05, indicating a significant effect of STEM learning on scientific literacy. These findings indicate that the STEM approach can create more active, contextual, and meaningful learning for students, especially through the integration of project activities and simple technology that facilitates the visualization of abstract concepts. Thus, science learning in elementary schools needs to be directed towards a more integrative, interactive, and student-centered model to encourage the strengthening of scientific literacy according to the demands of 21st-century competencies.